Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\sqrt{4\left(a-3\right)^2}=\sqrt{2^2\left(a-3\right)^2}=2\sqrt{\left(a-3\right)^2}=2.\left|a-3\right|=2\left(a-3\right)=2a-6\) (Vì \(a\ge3\) )
b) \(\sqrt{9\left(b-2\right)^2}=\sqrt{3^2\left(b-2\right)^2}=3\sqrt{\left(b-2\right)^2}=3\left|b-2\right|=3\left(2-b\right)\)
\(=6-3b\) (vì b < 2 )
b) \(\sqrt{27.48\left(1-a\right)^2}=\sqrt{27.3.16.\left(1-a\right)^2}=\sqrt{81.16.\left(1-a\right)^2}\)
\(=\sqrt{9^2.4^2.\left(1-a\right)^2}=9.4\sqrt{\left(1-a\right)^2}=36.\left|1-a\right|=36\left(1-a\right)=36-36a\) (vì a > 1)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)\(\sqrt{4-2\sqrt{3}}-\sqrt{3}=\sqrt{3-2\sqrt{3}+1}-\sqrt{3}\)
\(=\sqrt{\left(\sqrt{3}-1\right)^2}-\sqrt{3}=\sqrt{3}-1-\sqrt{3}=-1\)
b) \(\sqrt{11+6\sqrt{2}}-3+\sqrt{2}=\sqrt{9+6\sqrt{2}+2}-3+\sqrt{2}\)
\(=\sqrt{\left(3+\sqrt{2}\right)^2}-3+\sqrt{2}=3+\sqrt{2}-3+\sqrt{2}=2\sqrt{2}\)
c) \(\sqrt{25x^2}-2x=-5x-2x=-7x\)(vì x < 0)
d) \(x-5+\sqrt{25-10x+x^2}=x-5+\sqrt{\left(5-x\right)^2}=x-5+x-5=2x-10\) (vì x > 5)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(x^2-5x+3=0\)
Áp dụng định lí viet ta có: \(\hept{\begin{cases}x_1+x_2=5\\x_1x_2=3\end{cases}}\)
a) \(A=x_1^2+x_2^2=\left(x_1+x_2\right)^2-2x_1x_2=5^2-2.3=19\)
b) \(B=x_1^3+x_2^3=\left(x_1+x_2\right)^3-3\left(x_1+x_2\right)x_1x_2=5^3-3.5.3=80\)
c) \(C=\left|x_1-x_2\right|\)>0
=> \(C^2=x_1^2+x_2^2-2x_1x_2=19-2.3=13\)
=> C = căn 13
d) \(D=x_2+\frac{1}{x_1}+x_1+\frac{1}{x_2}=\left(x_1+x_2\right)+\frac{x_1+x_2}{x_1x_2}=5+\frac{5}{3}=5\frac{5}{3}\)
e) \(E=\frac{1}{x_1+3}+\frac{1}{x_2+3}=\frac{\left(x_1+x_2\right)+6}{x_1x_2+3\left(x_1+x_2\right)+9}=\frac{5+6}{3+3.5+9}=\frac{11}{27}\)
g) \(G=\frac{x_1-3}{x_1^2}+\frac{x_2-3}{x_2^2}=\left(\frac{1}{x_1}+\frac{1}{x_2}\right)-3\left(\frac{1}{x_1^2}+\frac{1}{x_2^2}\right)\)
\(=\frac{x_1+x_2}{x_1x_2}-3\frac{x_1^2+x_2^2}{x_1^2.x_2^2}=\frac{5}{3}-3.\frac{19}{3^2}=-\frac{14}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\sqrt{3-x}+\sqrt{2-x}=1\)
\(\Rightarrow\sqrt{3+x}=1-\sqrt{2-x}\)
\(\Rightarrow3+x=1-2\sqrt{2-x}+2-x\)
\(\Rightarrow2x+2\sqrt{2-x}=0\)
\(\Rightarrow x+\sqrt{2-x}=0\)
\(\Rightarrow2-x=\left(-x\right)^2\)
\(\Rightarrow2-x=x^2\)
\(\Rightarrow2-x^2-x=0\)
\(\Rightarrow x^2+x-2=0\)
\(\Rightarrow\orbr{\begin{cases}x+2=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-2\\x=1\end{cases}}}\)
Vậy....
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\sqrt{x^2-4x+4}=3\Leftrightarrow\sqrt{\left(x-2\right)^2}=3\)
\(\Leftrightarrow x-2=3\Leftrightarrow x=5\)
b, \(\sqrt{x^2-10x+25}=x+3\Leftrightarrow\sqrt{\left(x-5\right)^2}=x+3\)
\(\Leftrightarrow x-5=x+3\Leftrightarrow0\ne8\)( vô nghiệm )
Đáp án là D